ANALISIS STRATEGI PENGEMBANGAN USAHA KULINER DI MASA PANDEMI DENGAN METODE (SWOT) (STUDI KASUS RUMAH MAKAN DI KECAMATAN SUKOHARJO, KABUPATEN SUKOHARJO) - Ainur Komariah; Suprianto, Maria Puspita Sari (PROSEDING, 2022)
The COVID-19 virus outbreak resulted in a decline in all sectors, including the economic sector. The decline in the economy in Indonesia was caused by the decline in income in the MSME sector. One type of MSME that has experienced a decline in income is the restaurant business. This study aims to identify and analyze the restaurant business development strategy in Sukoharjo Regency during the pandemic. The respondents in this study were restaurant businesses registered with the Central Statistics Agency (BPS) of Sukoharjo Regency. The data analysis used is EFI Matrix, EFE and SWOT Analysis. The result of this study is the score obtained on the EFI Matrix is ​​2.92. While the score from the EFE Matrix is ​​2.85. The score shows that the restaurant business in Sukoharjo Regency is in quadrant 1 position and the SWOT analysis compiled from external internal factors produces 4 strategies, namely SO Strategy, WO Strategy, ST Strategy, and WT Strategy. Keywords: Restaurant, Strategy, SWOT Analysis.